Marcadores de estresse oxidativo e atividade das colinesterases em bovinos experimentalmente infectados por Babesia bovis, Babesia bigemina e Anaplasma marginale - Doyle, Rovaina Laureano (2015)
Babesiosis and anaplasmosis are part of the complex called Bovine Parasitic Sadness (TPB), a disease that causes high morbidity and mortality in susceptible cattle. It is caused by infection of Babesia bovis and Babesia bigemina protozoa and by the bacterium Anaplasma marginale. The objective of this study was to evaluate oxidative stress parameters in cattle experimentally infected with B. bovis and B. bigemina and the activities of cholinesterase in asymptomatic B. bigemina well as interference of splenectomy in the oxidative balance of cattle infected with A. marginale. For this, three experiments were performed, using 24 young cattle divided into three groups, each consisting of eight animals which: in the first experiment, four control and four infected with attenuated strain of B. bovis, which were observed decrease in erythrocytes count and activities of catalase (CAT) and superoxide dismutase (SOD) in addition to increased levels of thiobarbituric acid reactive substances (TBARS). In Experiment II, we used four cattle control and four infected with attenuated strain of B. bigemina, observed decrease in the activities of acetylcholinesterase (AChE), butyrylcholinesterase (BChE) and CAT, and increased levels of TBARS and SOD in infected cattle. And, in Experiment III, four splenectomized cattle and four intact, both groups infected with A. marginale, with no difference between groups in the hematological and enzymatic profile, only observed drop in hematocrit, red blood cell count and hemoglobin concentration, and increased total leukocyte count due to lymphocytosis in both groups. Positive correlations were found between TBARS versus bacteremia and negative between NPSH versus bacteremia in both groups, but the correlations were higher in splenectomized group. From the results it can be inferred that infection with B. bovis causes oxidative balance, in the same way B. bigemina infection induces an oxidative stress condition and changes the atividase cholinesterase even in asymptomatic animals and bacteremia by A. marginale influences lipid peroxidation in independent splenectomy cattle. This study may suggest that oxidative stress and low-grade inflammation markers can be used as auxiliary tool in the early diagnosis of this disease as well as the basis for studies on the use of antioxidants in the diet of cattle to prevent infection and / or reduce the severity of injuries caused by these parasites.